FENOMENA COURTESSY OF YOUTUBE DAN INTEGRITAS JURNALIS TELEVISI - Andriani, Fizzy (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
This day, almost every videos and pictures in Indonesia television station are using Youtube as a source. Even for their news programme. The using of Youtube in almost every programme is giving the bad name of journalism work. The credibility and integrity of television journalist are damage by the indolent work. Yes, Youtube is meant to help people to discover many things, but it doesnt meant that Youtube proficient to alter the function of television journalism.